The Influence of Product Quality, Prices, and Promotions on Costumer Satisfaction in Flolabel Boutiques in Rembang City - Gianti, Gianti; Suharti, Suharti (Economics and Business International Conference Proceeding, 2024)
This research aims to obtain empirical evidence and be able to analyze the influence of product quality, price, and promotion on costumer satisfaction. The population in this research is consumers who have purchased at Flolabel boutique. The total sample used in this research is 100 respondents using accidental sampling technique. Multiple linear regression analysis was used for data analysis. Research of this kind is quantitative in nature. Primary data from questionnaires was used as the data source for this study. So it can be concluded partially all independent variabels have a positive and significant effect on costumer satisfaction. Fcount value is 15.594 with Ftable of 2.70 and value the meaning of 0,000. A significance level below 0.05 is indicative. The regression model is significant and useful for forecasting the dependent variable